Light-Responsive, Shape-Switchable Block Copolymer Particles - Lee, Junhyuk; Ku, Kang Hee; Kim, Jinwoo; Lee, Young Jun; Jang, Se Gyu; Kim, Bumjoon J. (AMER CHEMICAL SOC, 2019)
A robust strategy is developed for preparing light-responsive block copolymer (BCP) particles in which shape and color can be actively controlled with high spatial and temporal resolution. The key to achieving light-responsive shape transitions of BCP particles is the design and synthesis of surfactants containing light-active groups (i.e., nitrobenzyl esters and coumarin esters) that modulate the amphiphilicity and interfacial activity of the surfactants in response to light of a specific wavelength. These light-induced changes in surfactant structure modify the surface and wetting properties of BCP particles, affording both shape and morphological transitions of the particles, for example from spheres with an onion-like inner morphology to prolate or oblate ellipsoids with axially stacked nanostructures. In particular, wavelength-selective shape transformation of the BCP particles can be achieved with a mixture of two light-active surfactants that respond to different wavelengths of light (i.e., 254 and 420 nm). Through the use of light-emitting, photoresponsive surfactants, light-induced changes in both color and shape are further demonstrated. Finally, to demonstrate the potential of the light-triggered shape control of BCP particles in patterning features with microscale resolution, the shape-switchable BCP particles are successfully integrated into a patterned, free-standing hydrogel film, which can be used as a portable, high-resolution display.
Keywords: POLYMER; VESICLES; NANOPARTICLES; EVOLUTION